(3GdaSGO GdEOGQj h GdeGdj (B:s (3eagheg CKGQg h WQb bjGSg h LghO ecGaMJg (B/s - (3GdQcjHGJ, cGjO cQjes ((3YeGf(B: s (3OGQ GdCjGe(B, s, 2015)
(3jJfGhd eaghe GdaSGO aj VhA eOdhd GdCjGJ GdbQBfjI GdcQjeI hCSHGH GdaSGO GdG OGQj hGdeGdj, CKQ GdaSGO GdEOGQj h GdeGdj aj GdJfejI, BdjGJ bjGS GdaSGO hBdjGJ ecGaMJg, GdLgGJ GdeJgeI HecGaMI GdaSGOYGdejG, Cge GdGJaGbjGJ h GdhKGFb GdOhdjI h GdYQHjI GdeJYdbI HGdaSGO(B.s
(3GdeQGLY U(B.259s
Keywords: (3GdEUdGM GdEOGQjs; (3GdaSGO GdEOGQjs; (3LQGFe GdCehGds